2010
DOI: 10.1021/ma100093b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Shear Thickening in Reversibly Cross-Linked Supramolecular Polymer Networks

Abstract: We report here the nonlinear rheological properties of metallo-supramolecular networks formed by the reversible cross-linking of semi-dilute unentangled solutions of poly(4-vinylpyridine) (PVP) in dimethyl sulfoxide (DMSO). The reversible cross-linkers are bis-Pd(II) or bis-Pt(II) complexes that coordinate to the pyridine functional groups on the PVP. Under steady shear, shear thickening is observed above a critical shear rate, and that critical shear rate is experimentally correlated with the lifetime of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
207
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(229 citation statements)
references
References 46 publications
(149 reference statements)
17
207
4
Order By: Relevance
“…53,54,60 They attribute the observed shear thickening in these systems to a shear-induced increase in the number of elastically effective network strands, which stems from the conversion of intrachain crosslinks to interchain crosslinks at high strains. 60 In collagen-based materials, Rajagopalan and co-workers ascribed a similar strain stiffening to deformation-induced reorganization of the dynamic noncovalent crosslinks to increase the number of elastically effective strands. 55 In the latter study, the dynamic crosslinks originate from H-bonding interactions between the collagen fibrils.…”
Section: ■ Discussionmentioning
confidence: 99%
“…53,54,60 They attribute the observed shear thickening in these systems to a shear-induced increase in the number of elastically effective network strands, which stems from the conversion of intrachain crosslinks to interchain crosslinks at high strains. 60 In collagen-based materials, Rajagopalan and co-workers ascribed a similar strain stiffening to deformation-induced reorganization of the dynamic noncovalent crosslinks to increase the number of elastically effective strands. 55 In the latter study, the dynamic crosslinks originate from H-bonding interactions between the collagen fibrils.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Craig and coworkers extensively studied the relationship of bond kinetics and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 13 polymer relaxation timescales, demonstrating that disadvantageous shear-thickening behavior arises if polymer relaxation occurs more rapidly than reconnection of broken crosslinks. [78][79] As such, the decreased polymer relaxation may be accomplished through formation of multifold junctions in highly modified guest-host hydrogels to enforce shear-thinning behavior and ease of injection. 80 The physical chemistry underlying the flow process, as well as other fundamental behaviors of supramolecular networks have been recently reviewed.…”
Section: Injectable Hydrogelsmentioning
confidence: 99%
“…They observed the shear thickening in a colloidal system with attractive interactions and found the transition to shear thickening flow is stress controlled and results in a fine suspension microstructure that produces enhanced modulus gels. Xu et al [9] added bis-Pd(II) or bis-Pt(II) complexes cross-linker to semidilute unentangled solutions of poly(4-vinylpyridine) (PVP) in dimethyl sulfoxide (DMSO). They reported that the onset and magnitude of the shear thickening depend on the amount of cross-linkers added.…”
Section: Introductionmentioning
confidence: 99%